Pengaruh Konservatisme Akuntansi Terhadap Relevansi Nilai Laporan Keuangan dengan Kualitas Laba Sebagai Variabel Moderasi - Amalia Zolehah; Riduan Mas'ud; Sanurdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aims of this study to examine the effect of conservatism on the value relevance of financial statements, and the ability of earnings quality as a moderating variabel to interact the relationship between conservatism and value relevance of financial statements. The principle of conservatism is prudance in financial reporting. Where the company does not immediately recognize and measure assets and profits as gains, and expenses and liabilities as losses.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange dor the 2020-2022 period. The sample are choises using the purposive sampling method and the research sample obtanied 62 companies. Hypothesis testing is done by using muliple linear regression method. The results show that the aplication of accounting conservatism had a positive effect on the value relevance. Meanwhile, the moderating variable earnings quality is not able to interact the conservatism realtionship to the value relevance of the financial statements. Future research is expected to be able to use the latest calculation models and other measurements, so that research results can show the latest application and impact of accounting conservatism on the value releance of financial statements with earnings quality as a moderating variabel.